2016
DOI: 10.1002/lary.26069
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and predictors of surgical management in type 1 laryngeal cleft swallowing dysfunction

Abstract: 4. Laryngoscope, 126:2838-2843, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 22 publications
3
46
1
Order By: Relevance
“…Almost all authors reported a high prevalence of co‐morbidities in patients with LC1. The most commonly reported medical conditions were gastro‐oesophageal reflux disease (GERD) in up to 70% of patients, and prematurity at birth in up to 36%, as well as asthma, chronic lung disease (CLD), laryngomalacia (LM), tracheo‐oesophageal fistula (TEF) and cardiovascular anomalies . Of particular note is the relatively high prevalence of LC in patients with oesophageal atresia (EA) with or without TEF.…”
Section: Presentationmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost all authors reported a high prevalence of co‐morbidities in patients with LC1. The most commonly reported medical conditions were gastro‐oesophageal reflux disease (GERD) in up to 70% of patients, and prematurity at birth in up to 36%, as well as asthma, chronic lung disease (CLD), laryngomalacia (LM), tracheo‐oesophageal fistula (TEF) and cardiovascular anomalies . Of particular note is the relatively high prevalence of LC in patients with oesophageal atresia (EA) with or without TEF.…”
Section: Presentationmentioning
confidence: 99%
“…This behoves the clinician to carefully rule out the presence of an oesophageal anomaly or TEF in patients with suspected LC1, since many TEF subtypes can in fact present subtly. Different series have also reported a wide variation (up to 30%‐50%) in associated neurological conditions and hypotonia . Several syndromes have also been linked to LC1 including VACTERL association, Pallister‐Hall syndrome, CHARGE association, Down syndrome, Opitz‐Frias syndrome, Townes‐Brock syndrome and Williams’ syndrome .…”
Section: Presentationmentioning
confidence: 99%
See 3 more Smart Citations